Determinación del Comportamiento Plaquetario en perros tratados, con Auto hemoterapia - Riera Narváez, Amanda Lisbeth (2023)
The work presented below consists of an experimental study in order to determine what are the alterations that it will produce in terms of platelets, this treatment being a conventional non-alternative technique that promises to stimulate the immune system. Auto hemotherapy treatment has several advantages in its use, unlike the risks to which patients are exposed when using conventional medications that can sometimes become immunosuppressive and cause side effects in patients. Several studies have shown that this technique presents good results when treating autoimmune diseases, but there are more studies that prove its efficacy in diseases of infectious origin such as papilomas presented in both cattle and dogs. The way in which Autohemotherapy (AHT) Works by introducing blood from the same pateen from one place to another and observing the phagocytic activity that occurs has already been mentioned in several studies. This field work was carried out, which consisted of studying 10 dogs, 5 with 5ml of blood and the rest with 3ml. Blood was extracted by venipuncture from the cephalic vein to later be reinjected into the same patient, but in the muscle, in the caudal area of the femur and perform a blood count after 24 to observe the changes that occur specifically in platelets. The treatment lasted for an interval of 5 weeks every 7 days. Regarding the results obtained in the blood counts of the patients with 5ml treatment, moderately notable changes were observed when compared with the platelet range that started the treatment and the patients with the 3ml treatment saw more noticeable alterations.